2021
DOI: 10.3389/fimmu.2021.661806
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and COVID-19: From Nutrition to Immunity

Abstract: Breastfeeding not only provides the optimum source of nutrients for the neonate and its first strong shield against infection but also lays the foundation for somatic and psychological bonding between the mother and child. During the current COVID-19 pandemic, although the guidelines of the relevant international and national agencies recommend breastfeeding by SARS-CoV-2–infected mothers, considerable insecurity persists in daily clinical practice regarding the safety of the infants and the perceived advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
20

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 73 publications
1
66
0
20
Order By: Relevance
“…sIgA is the most abundant antibody in breast milk that provides adequate specific protection against pathogens, including viruses. The specificity of sIgA depends on the maternal immune response to previous infection, which probably explains the low infection rate or milder symptoms seen in infected infants breastfed by mothers infected with SARS-CoV-2 [ 14 ]. A similar mechanism can be involved in the immune response after maternal vaccination [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…sIgA is the most abundant antibody in breast milk that provides adequate specific protection against pathogens, including viruses. The specificity of sIgA depends on the maternal immune response to previous infection, which probably explains the low infection rate or milder symptoms seen in infected infants breastfed by mothers infected with SARS-CoV-2 [ 14 ]. A similar mechanism can be involved in the immune response after maternal vaccination [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study reported that all breast milk samples were free of SARS-CoV-2 regardless of whether SARS-CoV-2 was positive or negative in specimens from the upper respiratory tract confirming previous reports. 31,32 In contrast, several earlier studies reported positive detection of SARS-CoV-2 RNA in breast milk from mothers with COVID-19. [33][34][35][36] Such conflicting data indicate that more comprehensive studies are required before advocating that breastfeeding is unsafe for mothers with confirmed or suspected infection with COVID-19.…”
Section: Discussionmentioning
confidence: 88%
“…The beneficial properties of breastfeeding including the practice of skin-to-skin care and the transfer of protective maternal antibodies via breast milk (especially secretory IgA (sIgA) and, to a lesser extent, IgM and IgG isotype immunoglobulins) are well established [22]. Recent evidence indicates that breastfeeding does not seem to be associated with neonatal SARS-CoV-2 infection because viral transmission through the milk, if any, should be rare [23] and because a robust sIgA-dominant SARS-CoV-2 antibody response is detectable in human milk soon after infection in a significant majority of individuals [24], suggesting a possible protection granted by the mothers to their infants [25][26][27][28][29][30]. Moreover, there is evidence in vitro suggesting whey proteins in human breastmilk as a direct-acting inhibitor of SARS-CoV-2 infection and replication [31].…”
Section: Discussionmentioning
confidence: 99%